2022
DOI: 10.3389/fmicb.2021.793441
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Processes and Geographic Distance in Regulating Local and Regionally Abundant and Rare Bacterioplankton in Lakes

Abstract: Bacteria are vital components of lake systems, driving a variety of biogeochemical cycles and ecosystem services. Bacterial communities have been shown to have a skewed distribution with a few abundant species and a large number of rare species. The contribution of environmental processes or geographic distance in structuring these components is uncertain. The discrete nature of lakes provides an ideal test case to investigate microbial biogeographical patterns. In the present study, we used 16S rRNA gene meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
(101 reference statements)
1
5
0
Order By: Relevance
“…Positive abundance–occupancy relationships have been noted for a wide range of taxa from bacteria to vertebrates (Shade et al 2018). The results presented here suggest that both the bacterial and eukaryotic assemblages in the surface sediments of lakes on a national scale follow the same pattern, a trend also observed for the bacterioplankton in a subset of these lakes (Pearman et al 2022 a ). The majority of the taxa found in this study where present only in one lake and had very low relative abundances.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Positive abundance–occupancy relationships have been noted for a wide range of taxa from bacteria to vertebrates (Shade et al 2018). The results presented here suggest that both the bacterial and eukaryotic assemblages in the surface sediments of lakes on a national scale follow the same pattern, a trend also observed for the bacterioplankton in a subset of these lakes (Pearman et al 2022 a ). The majority of the taxa found in this study where present only in one lake and had very low relative abundances.…”
Section: Discussionsupporting
confidence: 80%
“…However, even within reasonably short geographic distances they can experience diverse environmental conditions due to differences in parameters such as size, depth, geomorphology, and land use and geology in their catchment. The plankton communities of lakes have been extensively studied (Kraemer et al 2020; Schallenberg et al 2021; Pearman et al 2022a). Work involving sediments, has generally focused on paleolimnological studies, involving taxa that fossilize such as diatoms (Rühland et al 2003) and chironomids (Irvine et al 2012), although molecular approaches to assess other taxa are increasing (Capo et al 2022).…”
mentioning
confidence: 99%
“…The planktonic bacterial (Pbact) community had high proportions of Sporichthyaceae, within the class Actinobacteria. This group is frequently found to be abundant within lakes across the world ( Glöckner et al, 2000 ; Warnecke, Amann & Pernthaler, 2004 ; Jiao et al, 2018 ; Kraemer et al, 2020 ) and has previously been shown to be an important component in New Zealand lakes (which included the lakes assessed here; Pearman et al, 2022 ). The small size of the Actinobacteria, may protect them from protistan grazing ( Allgaier & Grossart, 2006 ) which, combined with their ability to degrade a variety of complex organic materials, makes them competitive in lake environments ( Ghai et al, 2014 ).…”
Section: Discussionmentioning
confidence: 85%
“…The small size of the Actinobacteria, may protect them from protistan grazing ( Allgaier & Grossart, 2006 ) which, combined with their ability to degrade a variety of complex organic materials, makes them competitive in lake environments ( Ghai et al, 2014 ). The family Comamonadaceae, class Gammaproteobacteria, was another taxa which contributed substantially to the Pbact and has also previously been shown to be abundant in freshwater environments ( Willems, 2014 ; Pearman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, stochastic processes or some uninvestigated important environmental variables might contribute to the patterns of the PMA-treated protistan and fungal communities (Wang et al, 2020). Additionally, deterministic processes may be more important for bacteria than eukaryotes in some freshwater systems (Pearman et al, 2022;Wan et al, 2023).…”
Section: Relic Dna Removal Changed the Relationships Between Microbia...mentioning
confidence: 99%